Correlation between gingival crevicular fluid levels of a disintegrin and metalloproteinase 8 and periodontal disease - Purva Chougule; Avni Raju Pradeep; Patil Rujuta; S Swathika (Wolters Kluwer Medknow Publications, 2022)
Background: Periodontal disease is an inflammation caused by host parasite interaction leading to the destruction of tooth supporting structures. During inflammation there is an elevated levels of biochemical signalling molecules. A disintegrin and metalloproteinase 8 (ADAM8) molecule has been implicated in various physiologic functions and pathologies. The expression of ADAM8 is upregulated in inflammatory conditions, and with upregulated expression they play a pivotal role in inflammation, immunity and osteoclastogenesis. Objective: To evaluate ADAM8 levels in gingival crevicular fluid (GCF) collected from healthy individuals and individuals with periodontal disease at baseline and in the periodontal disease group after nonsurgical periodontal therapy. Methods: In total, 48 subjects aged 20-65 years were divided into separate groups: a periodontally healthy group (group 1: males, n = 7, females, n = 9), a chronic gingivitis group (group 2: males, n = 6, females, n = 10), and a chronic periodontitis group (group 3: males, n = 8, females, n = 8). GCF samples were collected from all the groups at baseline and 3 months after nonsurgical periodontal therapy in the chronic gingivitis (group 4) and chronic periodontitis (group 5) cases. Statistical analysis was performed using Shapiro-wilk normality test, One way ANOVA test, Kruskal-Wallis test followed by Mann-Whitney U test, Spearman's rank correlation test and multiple linear regression analysis was done. The level of significance was determined at P < 0.05. Results: ADAM8 levels in the gingival crevicular fluid was significantly higher in group 3 (26,416.25 ± 7,817.59) than groups 1 and 2 at baseline at P < 0.001. After non-surgical periodontal therapy, ADAM8 levels in the gingival crevicular fluid was significantly reduced for group 2 (13,186.88 ± 3,247.62) and group 3 (18,375.63 ± 3,339.07) at P < 0.001. Conclusion: ADAM8 levels were increased in chronic gingivitis (group 2) and chronic periodontitis group (group 3) and reduced after non-surgical periodontal therapy in groups 2 and 3.